Hubungan Pemberian Edukasi Media Leaflet Dengan Mobilisasi Pasien Post Sectio Caesaria - Hastuti, Dwi; Wilis Dwi Pangesti (NERSMID : Jurnal Keperawatan dan Kebidanan, 2026)
Early mobilization is crucial for post-C-section patients. Failure to mobilize post caesarean section patients can result in delayed wound healing, infection, bleeding, obstructed blood flow, and impaired uterine involution. Therefore, patients need to gain knowledge about post caesarean  section mobilization, which can be obtained through education from healthcare professionals. This study aimed to examine the correlation between educational leaflet provision and early mobilization in post-CS patients. The study was conducted in the Postnatal Ward of RSUD (Regional Public Hospital) Prembun from March 4 to May 31, 2025. An analytic correlational design with a cross-sectional approach was employed. Sampling was carried out using purposive sampling. Research instruments included educational leaflets and a mobilization checklist. A total of 86 postpartum women within 0–2 hours post-CS without comorbidities were included, divided into those who received leaflet-based education and those who received verbal information only. Mobilization was evaluated using a checklist 24 hours post-CS. Data were analyzed using univariate and bivariate Spearman rank correlation tests. The majority of respondents were of reproductive age, had completed high school or higher education, and were multiparous. A total of 54 respondents (62.8%) performed early mobilization. Statistical analysis showed a significant correlation between leaflet-based education and early mobilization (p = 0.000, r = 0.446).